HEAVY METAL LEVELS OF MULBERRY (MORUS ALBA L.) GROWN AT DIFFERENT DISTANCES FROM THE ROADSIDES - M. Pehluvan; H. Karlidag; M. Turan (Journal of Animal and Plant Sciences, 2012)
The heavy metals pollution of mulberry cultivated soil, mulberry leaf and fruit, growing at different distances from the roadside were investigated in the Upper Coruh Valley of Turkey. The rate of heavy metals in soil, leaf and fruit were detected by Inductively Coupled Plasma Optical Emission Spectrophotometer (ICP-OES). All of the heavy metals (Zn, Mn, Cu, Co, Cr, Pb, Cd and Ni) were found in soil and parts of plant and their highest level at a distance of 20 m from the roadside. At a distance of 20 m from the roadside, the soil was found to be contaminated by Zn (330.7 mg kg-1), Cu (217.5 mg kg-1), Pb (500.2 mg kg-1) and Cd (4.24 mg kg-1) pollutants. The concentration of Pb in mulberry fruit was found to be more than the permissible limits at a 20 and 100 m distances from the roadside with its 0.467 and 0.419 mg kg-1 values, respectively. At all of distances, the concentration of Ni in fruit was found higher than the permissible limits. The results reflected a strong relationship between soil and fruits for contamination with some heavy metals.
Keywords: Morus alba L.; heavy metal pollution; the Upper Coruh Valley; Turkey